Could distress tolerance levels be associated with the severity of chronic spontaneous urticaria? - Gurok, Nese Gocer; Gurok, Mehmet Gurkan; Ozturk, Savas (Galenos Publ House, 2022)
Background and Design: Chronic spontaneous urticaria (CSU) is a common disease characterized by erythematous and itchy wheals, angioedema, or both that last for >6 weeks. Its etiology is not yet fully determined. This study aimed to analyze the distress tolerance (DT) levels of patients with CSU and correlations between DT and clinical parameters and other psychological symptoms.Materials and Methods: Fifty-two patients with CSU without any concomitant diseases were included in the study. The control group included 50 healthy volunteers with similar baseline demographics but without physical or psychiatric diseases. The urticaria activity score 7 (UAS7) was used to determine the disease severity in the patient group. In both groups, Sociodemographic and Clinical Data Form, Distress Tolerance Scale (DTS), Beck Depression Inventory (BDI), and state and trait anxiety inventory were used. Statistical differences in psychiatric scale scores were found between the patient and control groups, and a correlation was found between UAS7 and scale scores in the patient group.Results: No differences in sociodemographic variables were found between the patient and control groups. The DTS and subgroup score analysis revealed statistically significant differences between the patient and control groups. The DTS-total scores (p<0.001), DTS tolerance subdimension scores (p<0.001), DTS self-efficacy subdimension scores (p=0.002), and DTS regulation subdimension scores (p=0.02) were statistically lower in the patient group than in the control group. The BDI (p<0.01) and anxiety scores (state, p<0.001; trait, p=0.002) were also higher in the patient group than in the control group. Furthermore, a positive correlation was found between UAS7 scores and all scale scores.Conclusion: Psychological disorders are prevalent in patients with CSU and exhibit an interaction with the prognosis. Although the interaction is well-known, no clear multidisciplinary approach has been established for patients with CSU. In this study, DT was significantly reduced in patients with CSU, and a positive correlation may exist between disease severity and psychological symptoms. Thus, the evaluation of DT in patients with CSU could be addressed in psychotherapy and might be a beneficial criterion not only for the treatment but also for disease severity.
Sıkıntıya dayanma düzeyi kronik spontan ürtikerin şiddeti ile ilişkili olabilir mi?
Keywords: Anxiety; depression; distress tolerance